A Multiple Controllable Sol–Gel Preparation of 2D Silica Lamellar Composites Based on Azoimidazolium Surfactants. Issue 7 (8th February 2017) - Lin, Changxu; Xu, Mengchun; Zhang, Wei; Yang, Long; Xiang, Zheng; Hong, Jinjian; Liu, Xiangyang
Abstract : As an important method in the fabrication of nanoscale materials, the sol–gel reaction needs to be improved with respect to its controllability, convenience of use, and composition extensibility. This improvement is primarily based on the photoresponsiveness of the azo bond and the liquid crystal analog, which both originated from the azoimidazolium head. Using a series of azoimidazolium surfactants, an enhanced sol–gel strategy is developed. The formation manipulation of samples includes UV light exposure on precursor solutions, spin coating, drop casting and brushing. The substrates selected include: glass, 3D printed hard plastic parts, rubber, a flexible polydimethylsiloxane film, and the regenerated silk fibroin film. Characterization of X‐ray diffraction, electronic microscopes, differential scanning calorimetry, and atomic force microscope is performed on the samples. The authors find that the orderliness and its anisotropy of 2D silica lamellar composites are adjusted with photo, thermal, and mechanical manipulations. A temperature related transition and recovery of composite structures are discovered. Further utilizations of this strategy include the fabrication of Au nanoparticles wrapped inside a silica thin layer using anion exchange chemistry and the convenient drop casting technique facilitated by the extra ordering tendency of multiple interactions on the head. Abstract : A controllable sol–gel strategy toward 2D silica composites : Based on the unique structure and properties of azoimidazolium combining from the imidazolium and the azobenzene unit, a light, thermal, substrate, and mechanical control of the orderliness and its anisotropy of 2D silica lamellar composites are achieved. A method to fabricate Au nanoparticles wrapped inside 2D silica layer is also derived.